RANCANG BANGUN DAN IMPLEMENTASI WEBSITE KARANG TARUNA PADA DESA BALONGCABE KECAMATAN KEDUNGADEM KABUPATEN BOJONEGORO - Eka Pratiwi Wulandari (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2020)
The young organization (karang taruna) of Balongcabe in Kedungadem subdistrict, at Bojonegoro Regency, is a young organization formed by youths between Rukun Tetangga (RT) and Rukun Warga (RW) in Balongcabe. The publication of activities or agendas still use social media and it becomes the performance resistance of karang taruna in Balongcabe. The development of information media on karang taruna activities with a website offer various facilities in presenting informstion, speed and comfort, easebof access by the public using internet. The aims of this research is to build a website. The design method used data collection techniques through observation, interviews, literature study. System development techniques used the PIECES method (Performance, Information / Data, Economic, Control / Security, Efficiency, and Service). This website was built using the PHP programming language and MySQL database in interface design. The test result implements a Likert scale. Is is a psychometric scale and is commonly used in questionnaires. The scale most widely used in respondents. Furthermore, the test result show that the website is easy to understand in terms of appearance and menu.